Development of intelligent systems for well drilling and petroleum production - Morooka, C. K.; Guilherme, I. R.; Mendes, JRP (Elsevier B.V., 2001)
Domains where knowledge representation is too complex to be described analytically and in a deterministic way is very common in the petroleum industry, particularly in the field of exploration and production. In these domains, applications of artificial intelligence techniques are very suitable, especially in cases where the preservation of corporate and technical knowledge is important. The Laboratory for Research on Artificial Intelligence Applied to Petroleum Engineering (LIAP) at Unicamp, has, during the last 10 years, dedicated research efforts to build intelligent systems in well drilling and petroleum production fields. In the following sections, recent advances in intelligent systems, under development in the research laboratory, are described. (C) 2001 Published by Elsevier B.V. B.V.
Keywords: intelligent systems; petroleum engineering; petroleum well planning; well production; water injection; water production